Laboratory Investigation of Fatigue Characteristics of Asphalt Mixtures with Steel Slag Aggregates - Hassan Ziari; Shams Nowbakht; Sajad Rezaei; Arash Mahboob (Advances in Materials Science and Engineering)
There are many steel-manufacturing factories in Iran. All of their byproducts, steel slag, are dumped randomly in open areas, causing many environmentally hazardous problems. This research is intended to study the effectiveness of using steel slag aggregate (SSA) in improving the engineering properties, especially fatigue life of Asphalt Concrete (AC) produced with steel slag. The research started by evaluating the physical properties of the steel slag aggregate. Then the 13 types of mixes which contain steel slag in portion of fine aggregates or in portion of coarse aggregates or in all portions of aggregates were tested. The effectiveness of the SSA was judged by the improvement in Marshall stability, indirect tensile strength, resilient modulus, and fatigue life of the AC samples. It was found that replacing the 50% of the limestone coarse or fine aggregate by SSA improved the mechanical properties of the AC mixes.